121k views
2 votes
If tan A = { and tan B = 3calculate and simplify the following:?tan(A - B) = +

If tan A = { and tan B = 3calculate and simplify the following:?tan(A - B) = +-example-1
User John Stock
by
4.3k points

1 Answer

3 votes

We will employ the compound angle formula;


\tan (A-B)=(\tan A-\tan B)/(1+(\tan A)(\tan B))

We substitute the values for tanA and tanB to obtain;


\tan (A-B)=((4)/(3)-(3)/(5))/(1-(4)/(3)((3)/(5)))

After rearranging and simplifying, we obtain;


\tan (A-B)=+(11)/(3)

User Sason Ohanian
by
4.6k points